Prescription of Antibiotics to Treat Gonorrhoea in General Practice in Flanders 2009–2013: A Registry-Based Retrospective Cohort Study. (31st July 2017) - Schweikardt, Christoph; Goderis, Geert; Elli, Steven; Coppieters, Yves
Abstract : Background . General practitioners (GPs) as a group have been identified as playing an important role in gonorrhoea management in Flanders. Belgian guidelines recommended ceftriaxone or alternatively spectinomycin from 2008 onwards and azithromycin combination therapy since 2012. Objectives . This study investigates to which extent contemporary gonorrhoea treatment guidelines were followed. Methods . A retrospective cohort study (2009–2013) of antibiotic prescriptions for gonorrhoea cases registered in the Flemish Intego general practice database was carried out. The database is based on electronic health record routine registration by over 90 GPs using the software programme Medidoc. Results . Ninety-one gonorrhoea cases with ten chlamydia and one genital trichomonas coinfections in 90 patients were registered between 2009 and 2013. The proportion of cases with ceftriaxone and/or spectinomycin prescriptions rose from 13% (two of 15 cases) in 2009 to 56% (nine of 16 cases) in 2013. Combination therapy of ceftriaxone and/or spectinomycin together with azithromycin rose from 0 of 15 cases (0%) in 2009 to 7 of 16 cases (44%) in 2013. Conclusion . Although numbers are small, the results suggest that gonorrhoea therapy guideline adherence improved between 2009 and 2013.